Analisis Kualitas Air Laut Berdasarkan Parameter Fisika dan Kimia (Kekeruhan, DO, pH dan TDS) di Wilayah Perairan Jawa Tengah - Indah Nurhidayati; Aryanti Fitrianingsih; Amad Narto; Riyadini Utari; Shabrina Putri Chairandy; Anang Budi Nugroho (CV. Creative Tugu Pena, 2026)
The increase of shipping activities and the entry of domestic, agricultural, and industrial waste through large rivers carry organic and inorganic pollutant loads into the waters of Central Java, becoming a contributing factor to marine environmental pollution. This will affect the seawater quality so that it will damaging the ecosystem. Maintaining seawater quality is one of the most important things, so a scientific study was conducted by analyzing seawater quality based on Physical and Chemical parameters. The analysis was carried out using the Pollution Index (IP) Method and testing on turbidity, dissolved oxygen (DO), acidity level (pH) and Total Dissolved Solids (TDS). Seawater samples were taken at KSOP Semarang, Rembang Sea, Semarang Sea, Kendal Sea, Batang Sea, Cilacap Sea and Kebumen Sea at different times for three consecutive days. Turbidity measurements used a Thermo Scientific type TN-100 Turbiditymeter. TDS measurements used an Extech Instrument type Exstik II TDS Meter. DO measurements used a DO Meter AZ 8430. pH measurements used an OHAUS type Aquasearcher pH Meter. There are four areas which declared to meet the quality standards, those are KSOP Semarang IP value of 0.891, Semarang Sea with IP of 0.891, Batang Sea with IP of 0.970, and Kebumen Sea with IP of 0.851. While the other three seas indicate light pollution, namely the Rembang Sea with IP of 3.867, Kendal Sea with IP of 1.219, and Cilacap Sea with IP of 1.802. Factors influencing the seawater’s physical and chemical parameters include anthropogenic activities such as runoff from land, waste disposal, port activities, and coastal erosion, besides, natural factors including rainfall, river flow, and geological conditions. The impact of changes in physical and chemical parameters on marine ecosystems and human activities are reduction in marine tourism, sedimentation in shipping lanes and ports, reduced biodiversity also a disruption of marine ecosystems.